Enduring Roots : Encounters with Trees, History, and the American Landscape - Samuels, Gayle (Rutgers University Press, 1999)
Enduring Roots tells the stories of historic American trees, including the oak, the apple, the cherry, and the oldest of the world's trees, the bristlecone pine. These stories speak of our attachment to the land, of our universal and eternal need to leave a legacy, and demonstrate that the landscape is a gift, to be both received and, sometimes, tragically, to be destroyed.